(untitled) (Statistics, Optimization & Information Computing, 2026)
Background: Germany and Japan have "mirror" life insurance ecosystems with very old populations and long periods of low interest rates. From 2020 to 2022, these markets went through a "double-cycle" crisis: the biological and operational shocks of the COVID-19 pandemic, followed by a major shift in the macroeconomic trend. Objective: This study examines the differing resilience strategies of two mature markets, highlighting the impact of distinct regulatory frameworks, Germany’s Solvency II and Japan’s Standard Reserve system, on their adaptation to global instability. Methods: This research employs primary regulatory data from the Federal Financial Supervisory Authority (BaFin) and the Life Insurance Association of Japan (LIAJ) to conduct a comparative mixed-methods analysis. The analysis integrates a Pearson correlation matrix with a quasi-experimental Interrupted Time Series (ITS) design and counterfactual modelling to ascertain the causal impact of the 2022 macroeconomic shock. Main Points: The analysis identifies two path-dependent survival models: Japan (Commercial Agility): The market bounced back thanks to sales, as shown by the strong positive correlation between Gross Written Premiums (GWP) and new policies (r = 0.749). ITS modeling showed that the slope would speed up significantly after 2022, by 1.60 trillion per quarter. This was due to a shift in strategy to "Third Sector" (medical/cancer) products and a 31.9% allocation to foreign securities. Germany (Regulatory Fortification): Resilience was based on capital adequacy instead of volume. There was almost a perfect correlation (r = 0.944) between GWP and Solvency Capital Requirement (SCR) coverage, which rose to 526.0% in 2022. At the same time as this solvency "windfall," there was an "Interest Rate Paradox." Rising rates made regulatory ratios stronger, but they also destroyed the value of fixed-income portfolios, turning €51.6 billion in hidden reserves into €19.4 billion in net hidden liabilities.